RELATIONSHIP BETWEEN MOLECULE STRUCTURE AND COAL MATURITY OF BAYAH FORMATION BASED ON X-RAY DIFFRACTION ANALYSIS - Ardiansyah, Muhammad Iqbal; Hamdani, Ahmad Helman; Haryanto, Agus Didit (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
Coal is the richest source of energy used worldwide. Characterization of the structure of coal is one of the important things in studying the use of coal. X-Ray Diffraction (XRD) has been successfully used as a tool to study the molecular structure characteristics of coal with various coal ranks. There are five coal samples to be examined from the Bayah Formation in Lebak Regency, Banten. This study aims to measure the crystal structure parameters in coal and use them to predict coal maturity level. The results of XRD analysis showed that the five coal samples had the same crystal structure characteristics. The value of d002 is in the range of 3.87 to 3.96 Å, indicating that the studied sample has a low content of microcrystalline units. The measurement of carbon aromaticity (fa) values in the study area ranged from 0.67 to 0.76. There is a strong correlation between the value of coal maturity as measured by vitrinite reflectance (Ro) and the value of aromaticity; which is characterized by a correlation value of r of 0.88. Thus, the aromaticity (fa) value of XRD can be used to predict the maturity level of coal.